2017
DOI: 10.1080/13691058.2017.1340671
|View full text |Cite
|
Sign up to set email alerts
|

Performance, power and condom use: reconceptualised masculinities amongst Western male sex tourists to Thailand

Abstract: Each year large numbers of Western men travel to Thailand for sex tourism. Although many will use condoms during their sexual encounters, others will not, potentially exposing themselves to the risk of acquiring sexually transmitted infections, including HIV. Although sex tourism in Thailand has been well documented, the social drivers underpinning voluntary sexual risk-taking through the avoidance of condoms remain poorly understood. Engaging with R.W. Connell's concept of hegemonic masculinity and drawing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The diverse experiences of MWPWS also vary within different venues of the sex industry or based on different SFP patterns. Thus, for example, sex tourism in developing countries is often characterized by open-ended and enduring relationships between sex tourists and local WPS, which seldom facilitates intimate experiences for MWPWS (Bishop & Limmer, 2018;Prior & Peled, 2019). However, street-based SFP is usually referred to by MWPWS in straightforward terms of strictly sexual experiences (Durant & Couch, 2019).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…The diverse experiences of MWPWS also vary within different venues of the sex industry or based on different SFP patterns. Thus, for example, sex tourism in developing countries is often characterized by open-ended and enduring relationships between sex tourists and local WPS, which seldom facilitates intimate experiences for MWPWS (Bishop & Limmer, 2018;Prior & Peled, 2019). However, street-based SFP is usually referred to by MWPWS in straightforward terms of strictly sexual experiences (Durant & Couch, 2019).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…Other factors associated with reduced usage were the belief that foreign condoms were of poorer quality [34], spontaneous sexual encounters or embarrassment at purchasing condoms [43], substance use [15,32,43], and travel to Latin America or the Caribbean [15]. An examination of male sex tourists to Thailand also revealed that unprotected sex was seen as more masculine and enjoyable, and there was a general misconception among male sex tourists that unprotected heterosexual intercourse was a low risk activity [44]. This same study also showed that male heterosexual sex tourists were aware of risks, but due to their own personal or peer experiences being at variance with the warnings they received regarding risky sexual behaviour, they were more likely to engage in unprotected sex with CSW.…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%
“…Pritchard and Morgan (2000) argued that this is because of a privileged landscape, where it is often the case of solo men undertaking tourism activities, which Coston and Kimmel (2012) call a “performance of masculinity”. This is evident across a range of tourism activities such as cycling tourism (Buning and Gibson, 2016), motorcycling (Frash et al , 2018) and sex tourism (Bishop and Limmer, 2018). Each of these genres tends to characterise the Western male as an individual of power, resource and are, therefore, accorded (un)conscious masculinity, although the presence of solo women in some of these spaces is slowly emerging (Doran, 2016; Martin et al , 2006; Weichselbaumer, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%